Influence of the Interaction Between Phosphoric Acid and Catalyst Layers on the Properties of HT‐PEFCs1. Issue 5 (4th March 2014) - Liu, F.; Mohajeri, S.; Di, Y.; Wippermann, K.; Lehnert, W.; Jones, Deborah; Jaouen, Frederic; Taillades‐Jacquin, Mélanie; Bucheli, Olivier
Abstract The performance of high‐temperature polymer electrolyte fuel cells is influenced by the components in the cell. In order to determine the effects of the platinum loading and the thickness of the anode and the cathode as well as of the phosphoric acid content on the cell performance, a three‐level factorial plan encompassing 15 experimental points was designed and carried out. The experimental results were analyzed statistically and expressed as graphic cubes in the range studied. It was found that each factor and their interactions have strong effects on the cell performance. The interactions are attributed to the distribution of phosphoric acid and gases in the membrane electrode assembly. The water vapor transport influences the concentration of phosphoric acid, which modifies not only the proton conductivity but also the cathode kinetics. The optimized cell performance was obtained with an acid amount of 20 mg cm–2, a cathode thickness of 125 μm (platinum loading of 1.0 mg cm–2), and an anode thickness of 75 μm (platinum loading of 0.6 mg cm–2).